Diversity and taxonomy of Tricholoma species from Yunnan, China, and notes on species from Europe and North America. (2nd November 2018) - Reschke, Kai; Popa, Flavius; Yang, Zhu L.; Kost, Gerhard
ABSTRACT: Although taxonomic knowledge on Tricholoma (Agaricales, Basidiomycota) is fairly comprehensive in northwest Europe, knowledge of the global diversity and distribution of Tricholoma spp. is still sparse. In this study, the diversity and distribution of some Tricholoma spp. are analyzed by morphological and molecular methods based on 70 collections from Yunnan, China, 45 from central Europe, 32 from Colorado, USA, 9 from Japan, and 3 from Ukraine. A Holarctic distribution is suggested for several species, based on collections and nuc rDNA internal transcribed spacer ITS1-5.8S-ITS2 (ITS) sequences. Six species new to science are formally described from Yunnan: five in existing sections, Tricholoma forteflavescens, T. olivaceoluteolum, T. melleum, T. olivaceum, and T. sinoportentosum, and one, T. muscarioides, in the newly described section Muscaria alongside several previously described species. Additional putatively new species cannot be formally described because they lack sufficient material. Tricholoma foliicola is recognized as a species of the genus Gerhardtia .